Measurement of physicochemical properties of green aqueous amino acid‐based ionic liquids and their correlation with temperature and concentration. Issue 2 (2nd December 2022) - Nashed, Omar; Talib, Nur Khairunnisa; Lal, Bhajan; Ghanem, Ouahid Ben; Mohshim, Dzeti Farhah; Sabil, Khalik M.; Shariff, Azmi Mohd
Abstract: Ionic liquids have attracted immense attention due to their unique properties and potential industrial applications. Green ionic liquids such as amino acid‐based ionic liquids (AAILs) are promising solvents due to their proven low toxicity. The properties of newly known substances are unavailable, especially when they are in aqueous solutions. This information is essential, and they must be understood before employing these materials in any application for technical, safety, and economical reasons. In this study, three types of AAILs were examined, namely; 1‐octyl‐3‐methylimidazolium glycine [OMIM][Gly], 1‐octyl‐3‐methylimidazolium alanine [OMIM][Ala], and 1‐octyl‐3‐methylimidazolium proline [OMIM][Pro]. The aqueous solutions were prepared at concentrations of 1, 10, 20, and 30 wt.%. The pH and electrical conductivity were measured at room temperature and atmospheric pressure. Moreover, volumetric properties such as density, molar volume, excess molar volume, and thermal expansion were also determined at atmospheric pressure over a temperature range of 298.15–338.15 K. An empirical correlation was also developed to correlate the volumetric parameters with temperature and concentration. The results showed that AAILs solutions are alkaline in nature. Moreover, they increase the electrical conductivity of water. Additionally, molar volume, excess molar volume, and isobaric thermal expansion increased as the temperature increased, whereas the density decreased with an increase in temperature. A discussion on the effect of anions was presented. The developed empirical correlation exhibited an accurate prediction of the volumetric properties with R 2  > 0.9762.